PUBLIC-PRIVATE PARTNERSHIP AS A TOOL FOR ATTRACTING INVESTMENTS IN THE DEVELOPMENT OF REGIONAL INFRASTRUCTURE OF UKRAINE - Kravchenko, Mykola (SWorld-Ger Conference proceedings, 2022)
The basis for ensuring the economic security of the regional infrastructure is its innovation and investment development. In order to accelerate the innovative development of business entities in the agrarian sector, state support programs are of great im